2000
DOI: 10.1074/jbc.m004796200
|View full text |Cite
|
Sign up to set email alerts
|

Flagellin from an Incompatible Strain of Pseudomonas avenae Induces a Resistance Response in Cultured Rice Cells

Abstract: The host range of Pseudomonas avenae is wide among monocotyledonous plants, but individual strains can infect only one or a few host species. The resistance response of rice cells to pathogens has been previously shown to be induced by a rice-incompatible strain, N1141, but not by a rice-compatible strain, H8301. To clarify the molecular mechanism of the host specificity in P. avenae, a strain-specific antibody that was raised against N1141 cells and then absorbed with H8301 cells was prepared. When a cell ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 63 publications
3
92
0
Order By: Relevance
“…During the past, several flagellin peptide variants have been discovered that do not elicit defense responses in A. thaliana Pfund et al 2004;Sun et al 2006). Furthermore, the so-called broad-species active flg22 peptide did not trigger defense responses in rice cell cultures, whereas they are responsive to a specific flagellin from the incompatible strain P. avenae Che et al 2000). It remains an open question what selective forces drive evolution of PAMP receptors such as the flagellin receptor into different directions.…”
Section: Discussionmentioning
confidence: 99%
“…During the past, several flagellin peptide variants have been discovered that do not elicit defense responses in A. thaliana Pfund et al 2004;Sun et al 2006). Furthermore, the so-called broad-species active flg22 peptide did not trigger defense responses in rice cell cultures, whereas they are responsive to a specific flagellin from the incompatible strain P. avenae Che et al 2000). It remains an open question what selective forces drive evolution of PAMP receptors such as the flagellin receptor into different directions.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the specific recognition molecules that are related to the induction of these immune responses in cultured rice cells, a strain-specific antibody was raised against the avirulent strain and then absorbed with the virulent strain. The specific antibody detected the flagellin protein, which is structurally different between the virulent and avirulent strains of A. avenae (21). Flagellin purified from the avirulent N1141 strain induced rice immune responses, whereas flagellin purified from the virulent K1 strain did not induce these responses.…”
mentioning
confidence: 99%
“…9,10,11,12 Among these PAMPs, flagellin, a main component of the bacterial flagellum, has been the most extensively studied in regards to the recognition mechanism and signal transduction. 13,14,15,16 We previously reported that flagellin from the rice avirulent N1141 strain of gram-negative phytopathogenic bacterium, Acidovorax avenae, induces PTI including H 2 O 2 generation, while flagellin from the rice virulent K1 strain of A. avenae does not induce. 14 16 Interestingly, mass spectrometry analysis using flagellins from the NDFlaA-KFlaA (K1 flagellin expression vector-possessing NDFlaA, N1141 flagellin deficient strain), KDFlaA-NFlaA (N1141 flagellin expression vector-possessing KDFlaA, K1 flagellin deficient strain) revealed that the molecular weight of each glycan chain in K1 flagellin is predicted to be 540, while the molecular weight of each glycan chain in N1141 flagellin is estimated to be 550.…”
Section: Specific Induction Of Pti By Flagellin Of a Avenaementioning
confidence: 99%
“…13,14,15,16 We previously reported that flagellin from the rice avirulent N1141 strain of gram-negative phytopathogenic bacterium, Acidovorax avenae, induces PTI including H 2 O 2 generation, while flagellin from the rice virulent K1 strain of A. avenae does not induce. 14 16 Interestingly, mass spectrometry analysis using flagellins from the NDFlaA-KFlaA (K1 flagellin expression vector-possessing NDFlaA, N1141 flagellin deficient strain), KDFlaA-NFlaA (N1141 flagellin expression vector-possessing KDFlaA, K1 flagellin deficient strain) revealed that the molecular weight of each glycan chain in K1 flagellin is predicted to be 540, while the molecular weight of each glycan chain in N1141 flagellin is estimated to be 550. The K-type flagellin purified from the NDFlaA-KFlaA strain induced immune responses such as H 2 O 2 generation, while the flagellin from the KDFlaA-NFlaA strain did not induce H 2 O 2 to the same degree as the K1 wild-type flagellin.…”
Section: Specific Induction Of Pti By Flagellin Of a Avenaementioning
confidence: 99%